The mechanism of concentric HfO2/Co3O4/TiO2 nanotubes investigated by intensity modulated photocurrent spectroscopy (IMPS) and electrochemical impedance spectroscopy (EIS) for photoelectrochemical activity. (November 2019) - Huai, Xiaochen; Girardi, Leonardo; Lu, Ran; Gao, Shang; Zhao, Yu; Ling, Yunhan; Rizzi, Gian Andrea; Granozzi, Gaetano; Zhang, Zhengjun
Abstract: In this work, we describe the preparation and photoelectrochemical (PEC) properties of concentric HfO2 /Co3 O4 /TiO2 nanotubes (NTs). From a methodological point of view, we demonstrated, for the first time, that intensity modulated photocurrent spectroscopy (IMPS) and electrochemical impedance spectroscopy (EIS) efficiently complement and can be highly valuable to optimize PEC water-splitting devices. We verified that the CSC and CH values (the capacitance of space charge region and Helmholtz layer, derived from a phenomenological equivalent circuits model, ECM) are of similar magnitude and that the CH can be affected by applied bias, the nature of the catalytic material and the passivation layer. The calculated CH /(CH  + CSC ) are in agreement with the high frequency intercept (HFI) derived by the IMPS experimental data. The charge transfer efficiencies (ղtr ) were obtained from the IMPS and ECM data: the ղtr values for HfO2 /Co3 O4 /TiO2 -NTs increased to 80.4% (0 V vs Ag/AgCl) compared to those in Co3 O4 /TiO2 -NTs (56.9%, 0 V vs Ag/AgCl) and in TiO2 -NT (25.6%, 0 V vs Ag/AgCl). We proved that the excellent PEC properties of HfO2 /Co3 O4 /TiO2 -NTs are due to i) the band alignment between small bad gap of Co3 O4 and TiO2 semiconductors, ii) increased hole transfer efficiency ղtr caused by excellent catalytic properties of Co3 O4 and iii) the passivation effect on surface defects of a HfO2 layer with appropriate thickness. Graphical abstract: The mechanism for the photoelectrochemical activity of HfO2 /Co3 O4 /TiO2 -NTs was studied in detail by the complementary use of Intensity Modulated Photocurrent Spectroscopy (IMPS) and Electrochemical Impedance Spectroscopy (EIS).Image 1 Highlights: The complementarity between intensity modulated photocurrent spectroscopy (IMPS) and electrochemical impedance spectroscopy (EIS) is shown. The catalytic properties of Co3 O4 and shielding effect of HfO2 layer are clearly deduced from EIS and IMPS spectra. The influence of heat treatments on the PEC properties of this photoanode was also investigated.